2019
DOI: 10.1007/s10902-019-00114-w
|View full text |Cite
|
Sign up to set email alerts
|

Savoring and Dampening with Passion: How Passionate People Respond when Good Things Happen

Abstract: AcknowledgementsThis is a pre-print of an article published in the Journal of Happiness Studies. The final authenticated version is available online at: https://doi. AbstractHow do people react when they experience a positive event while pursuing a passionate activity?In this research, we conducted three studies to test if the extent to which people respond to positive events by engaging in savoring (i.e., attempting to maintain or enhance positive emotions) and dampening (i.e., attempting to down-regulated or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 41 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…Sample 2. We recruited university students using the participation pool of a Canadian university as part of a larger project about academic and favorite activities (Schellenberg & Gaudreau, 2020). A total of 561 students participated in the study but 32 multivariate outliers, nine who reported not having answered the survey honestly, and 11 who did not answer the honesty-check question were removed from our analyses.…”
Section: Participantsmentioning
confidence: 99%
“…Sample 2. We recruited university students using the participation pool of a Canadian university as part of a larger project about academic and favorite activities (Schellenberg & Gaudreau, 2020). A total of 561 students participated in the study but 32 multivariate outliers, nine who reported not having answered the survey honestly, and 11 who did not answer the honesty-check question were removed from our analyses.…”
Section: Participantsmentioning
confidence: 99%
“…2 This data set was collected as part of a larger project on the experiences of sport fans. All other reports from this larger project focus on different variables and test different hypotheses (e.g., Schellenberg & Gaudreau, 2020). This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Methodsmentioning
confidence: 99%
“…Dropout intention was measured with three items (e.g., "I considered dropping out of graduate school") similar to those using in previous research (Schellenberg & Gaudreau, 2020).…”
Section: Dropout Intentionmentioning
confidence: 99%